Synchronize Speed Control for Multiple DC Motors Using Linear Quadratic Regulator - Muhammad Salihin, Saealal; A.T., Ramachandran; M. F., Abas; N., Md.Saad (Springer, 2017)
Abstract Direct Current (DC) motors have been extensively used iti many industrial applications. Therefore, the control of the speed of a DC mo lor is an important issue and has. been studied since the early decades in the last century. ProportionaI-Integrated-Derivative (PLD) controller is one of the methods to control synchronize multiple motor. But the settling time is slow for this controller and its affect the performance too, This paper presents Linear Quadratic Regulator (LQK) controller which is another meLhod of control synchronize multiple motor Lo reduce the settling time of the multiple motor using MATLAB software. The settling time result of the L.QR controller is compared with PTD controller.